Pensamiento arqueológico e historia de la investigación sobre las manifestaciones rupestres canarias - Farrujia de la Rosa, A. José (Complutum, 2009)
The research on the history of Canarian rock art, within the North African and European contexts, presents major problems, both theoretical and methodological. Facing this topic, in this paper we analyze, from a historical and diachronic perspective, which has been the evolution of research on Canarian rock art, focussing on the current situation and on the theoretical and methodological problems associated with this parcel of archaeological research. We will also address the connections that have been established between the Canary Islands, North Africa and the Atlantic area, paying attention to the theoretical models developed to explain these relationships. Therefore, this paper analyzes a period of seven centuries (XIVth-XXth), but will mainly focus on the scientific research generated from the late nineteenth century up to the present.